PENDUGAAN PERIODE KER1NG DAN AWAL MUSIM HUJAN UNTUK MEMPERBAIKI WAKTU TANAM KAPAS DI JAWA TIMUR - PRIMA D. RJAJAYA; M. SHOLEH; S. MULYANINGSIH; M. CHOLID; N. SUDIBYO; SOEBANDRJJO SOEBANDRJJO (Jurnal Penelitian Tanaman Industri, 1999)
Prediction of dryspell and the onset of rainy season to im¬ prove cotton planting time in East JavaClimatic elements paticularly rainfall strongly influences successful prediction of rainfed cotton yield. Rainfall variability varies amongst the seasons. Thepreviousplantingtimcs were determined based in 10 years daily rainfall data (1975-1984). Longterm rainfall data are required for rainfall analysis to get reliable probabilities The rainfall analysis was done using Markov Cham First Order Probability and dryspcll probability methods. The rainfall data were collected from 17 rainfall stations in East Java (Banyuwangi, Situbondo. Probolinggo, Jember, Lumajang, Pasuruan, Mojokerto.Tuban and I -amongan). The planting times varied from the first week to the fouth week of December for Pasuruan, Probolinggo. Situbondo, Jember. and Banyu¬ wangi: for these areas sequential system of cotton ater maize is not recom¬ mended due to short rainy season The planting times in Lumajang. Lanongan. Mojoketo. and Tuban ranged from mid December to early January, sufficient length of rainy season suppoted sequential system in these areas. The improved cotton planting times were 1 -2 weeks earlier or later than the previous planting times.